1998
DOI: 10.1093/emboj/17.7.2067
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila CtBP: a Hairy-interacting protein required for embryonic segmentation and Hairy-mediated transcriptional repression

Abstract: hairy is a Drosophila pair-rule segmentation gene that functions genetically as a repressor. To isolate protein components of Hairy-mediated repression, we used a yeast interaction screen and identified a Hairyinteracting protein, the Drosophila homolog of the human C-terminal-binding protein (CtBP). Human CtBP is a cellular phosphoprotein that interacts with the C-terminus of the adenovirus E1a oncoprotein and functions as a tumor suppressor. dCtBP also interacts with E1a in a directed yeast two-hybrid assay.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
288
2
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(309 citation statements)
references
References 82 publications
16
288
2
3
Order By: Relevance
“…To evaluate the contribution of the E1A carboxylterminus, we constructed two mutants containing: (i) a deletion removing the last 52 amino acids of E1A (DC52); and (ii) alanine substitutions in the C-terminal CtBP-interaction motif (LDL-A4) (Schaeper et al, 1995(Schaeper et al, , 1998. The biological function of CtBP is not yet clear, but data derived from studies in Drosophila suggest that it is a co-factor of transcriptional repressors like Hairy, Snail, Knirps, KruÈ ppel and Enhancer of split (Nibu et al, 1998a,b;Poortinga et al, 1998). Deletion mutants of E1A lacking the CtBPinteraction domain have enhanced tumorigenic potential suggesting that CtBP may be a negative regulator of E1A (Boyd et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the contribution of the E1A carboxylterminus, we constructed two mutants containing: (i) a deletion removing the last 52 amino acids of E1A (DC52); and (ii) alanine substitutions in the C-terminal CtBP-interaction motif (LDL-A4) (Schaeper et al, 1995(Schaeper et al, , 1998. The biological function of CtBP is not yet clear, but data derived from studies in Drosophila suggest that it is a co-factor of transcriptional repressors like Hairy, Snail, Knirps, KruÈ ppel and Enhancer of split (Nibu et al, 1998a,b;Poortinga et al, 1998). Deletion mutants of E1A lacking the CtBPinteraction domain have enhanced tumorigenic potential suggesting that CtBP may be a negative regulator of E1A (Boyd et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that RNAi depletion of the single Drosophila GRASP homologue (dGRASP) or its partner dGM130 does not lead to an apparent separation of the paired Golgi stacks. 12,51 Furthermore, the single CtBP/BARS homologue that exists in Drosophila (dCtPB) has been shown to mediate transcription repression regulating embryonic development, [67][68] but thus far, no link to the Golgi organization has been reported.…”
Section: The Golgi Ribbon Unlinking G 2 /M Checkpoint Is Conserved Inmentioning
confidence: 99%
“…Drosophila factors functionally characterized as short-range repressors all interact with CtBP, although it has not been established that all factors that bind the co-factor are necessarily short-range repressors. The longrange repressor protein Hairy, in particular, is thought to interact with CtBP, although this might be in an antagonistic mode (Poortinga et al, 1998;Zhang and Levine, 1999).…”
Section: Introductionmentioning
confidence: 99%